Alfalfa saponins inhibit oxidative stress-induced cell apoptosis through the MAPK signaling pathway. (31st December 2022) - Cui, Yalei; Li, Fen; Zhu, Xiaoyan; Xu, Junying; Muhammad, Abaidullah; Chen, Yanyan; Li, Defeng; Liu, Boshuai; Wang, Chengzhang; Wang, Zhichang; Ma, Sen; Liu, Xule; et al.
ABSTRACT: Background: Oxidative stress could seriously affect the growth performance of piglets. As natural extracts of Alfalfa (Medicago sativa), alfalfa saponins have been shown to function as antioxidants in piglets in vivo . However, few studies have investigated the effects and mechanism of alfalfa saponins against oxidative stress in piglet cells in vitro . In the current study, piglets' small intestinal epithelial cell line (IPEC-J2) was explored to investigate the protective effects of alfalfa saponins on injured cells induced by H2 O2 . Methods: To investigate the effects and mechanism of alfalfa saponins against oxidative stress in piglet cells, the cell viability, activity of antioxidant enzymes, LDH and the amount of MDA were detected in H2 O2 -treated cells after the cells were pre-incubated with alfalfa saponins. The mechanism of alfalfa saponins against H2 O2 -induced oxidative cell damage was explored by detecting the expression of mitochondrial apoptosis-related proteins. Furthermore, the signaling pathway of alfalfa saponins in IPEC-J2 cells under oxidative stress was also investigated. Results: The results indicated that alfalfa saponins could rescue cell viability, elevate the activity of antioxidant enzymes and down-regulate the activity of LDH and the amount of MDA in H2 O2 -induced cells. Conclusion: Alfalfa saponins could inhibit oxidative stress-induced cell mitochondrial apoptosis through the MAPK signaling pathway, thereby providing a new method for improving antioxidant stress ability by means of nutritional regulation.